Africa's animal giants - McCauley, Jane R., 1947- (Books for young explorers, 1987)
Introduces the physical characteristics and habits of some of the largest animals native to Africa including the elephant, giraffe, hippopotamus, rhinoceros, gorilla, Cape buffalo, lion, and ostrich.